The Nigerian novel and the postcolonial city - Mamudu, Clement Oshogwe (Department of English Language and Literature, 2022)
This thesis is a critical inquiry into the nature of the postcolonial African city as represented in fiction. It examines how the Nigerian novel represents the postcolonial African city and the extent to which it confirms or contests the dominant paradigms of scholarship in urban studies. In it, perspectives from urban studies are brought into conversation with literary representations of the postcolonial African city in contemporary Nigerian fiction thereby creating a nuanced synthesis of postcolonial literary studies and urban scholarship. Its provocative argument is that the postcolonial African city is both functional and legible despite its arguably squalid state and the undesirable living conditions of its subjects. Approaches that denigrate so-called Third World cities as particularly dystopic and illegible do not present the whole picture and are therefore one-sided and misleading. The Nigerian novel, it argues, reflects the need for rethinking of the dominant templates of urban studies to take into consideration the particularities and complexities of postcolonial cities. The thesis examines representations of the postcolonial city in four recent Nigerian novels: Ben Okri's The Famished Road (1991), Okey Ndibe's Arrows of Rain (2000), Chris Abani's GraceLand (2004), and Sefi Ata's Everything Good Will Come (2006). The selected novels' analyses foreground the argument that there is no universal template for theorizing the city; hence, there is a legitimate basis for talking about the postcolonial city both in conception and fictional representation. The thesis begins with an introduction which encompasses the aim, focal question, rationale, design/structure and the definition of key terms. This is followed by Chapter One which gives an insight into the state of the research field. The chapter reviews relevant scholarship with a view to situating modernity and the postcolonial city in Africa. In Chapters Two, Three, Four and Five, the primary texts, under various subtitles, are analyzed. The novels' representation(s) of the postcolonial (African) city, from different perspectives – like the problematic of legibility and spatial morphology, infrastructure, agency, urban governmentality, etc. – are critically examined. Chapter Six examines the place of bars and gender in determining the metro poetics of the postcolonial African city and how they are depicted in the selected novels. This is followed by the Conclusion, which summarizes the thesis by restating and highlighting its major argument and the ways in which it is elaborated upon in the fictional texts analyzed in the various chapters.